2018
DOI: 10.1021/acs.iecr.7b03795
|View full text |Cite
|
Sign up to set email alerts
|

NMR Speciation of Aqueous MAPA, Tertiary Amines, and Their Blends in the Presence of CO2: Influence of pKa and Reaction Mechanisms

Abstract: The diamine 3-(Methylamino)propylamine (MAPA) and eight tertiary amines were studied as single and blended aqueous CO2 absorbents at different concentrations and ratios to investigate the reaction mechanisms. After absorption (40 °C) and desorption (80 °C) experiments, quantitative 13 C NMR experiments were performed on each liquid sample.After absorption, the following CO2-derived species were identified and quantified:(bi)carbonate in each amine system; primary and secondary MAPA carbamate, and MAPA dicarbam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…11). Similarly to other MAPA-tertiary amine blends [41], the species identified and quantified at equilibrium were MAPA/MAPA(H + )2, primary MAPA carbamate (MAPA(H + )COO(p)), secondary MAPA carbamate (MAPA(H + )COO(s)) and MAPA di-carbamate (MAPA(COO )2), tertiary amine, tertiary amino carbonate and (bi)carbonate (HCO3 / (2HE)PRLD blended with MAPA was 14.4%, 11.2% and 11.4%, CO 2 ). In Fig.…”
Section: Tertiary Amine-mapa-h2o-co2 Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…11). Similarly to other MAPA-tertiary amine blends [41], the species identified and quantified at equilibrium were MAPA/MAPA(H + )2, primary MAPA carbamate (MAPA(H + )COO(p)), secondary MAPA carbamate (MAPA(H + )COO(s)) and MAPA di-carbamate (MAPA(COO )2), tertiary amine, tertiary amino carbonate and (bi)carbonate (HCO3 / (2HE)PRLD blended with MAPA was 14.4%, 11.2% and 11.4%, CO 2 ). In Fig.…”
Section: Tertiary Amine-mapa-h2o-co2 Systemsmentioning
confidence: 99%
“…Liquid samples collected from the low-pressure VLE apparatus were examined by means of NMR spectroscopy to characterise the species at equilibrium. In particular, the species concentrations were measured by acquiring quantitative 13 C NMR experiments at T = 300.0 K on a Bruker 600 MHz Avance III HD instrument equipped with a 5-mm cryogenic CP-TCI z-gradient probe, using the same method as described in Perinu et al [41].…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary amines cannot react with CO2 directly, although a limited number of authors have observed the formation of alkyl carbonate in aqueous tertiary alkanolamines. 11,[20][21][22][23] Jørgensen and Faurholt 20 suggested the reaction (2) in basic aqueous solutions of amino alcohols, and proposed the overall reaction (3) (which represents the inverse of the alkyl carbonate hydrolysis) as they observed the formation of the alkyl carbonate when mixing amines, bicarbonate and carbonate.…”
Section: R1r2nh + Co2 + B R1r2ncoo -+ Bh +mentioning
confidence: 99%
“…In particular, blends containing 3-(methylamino)propylamine (MAPA) and tertiary amines (referred also as third generation solvents) showed much better performance compared to traditional MEA-based solvents, both in terms of cyclic capacity and regeneration energy requirements [12,13]. The chemical mechanism involved behind the CO 2 absorption in this type of blended systems has been thoroughly characterized by Perinu et al [14]. Knuutila et al [15] reported 3 blends of MAPA with different tertiary amines (diethylethanolamine, DEEA; 1-(2hydroxyethyl)pyrrolidine, HEPP; 3-(diethylamino)-1,2-propanediol, DEA-PD) showing 30% lower reboiler duties (2.5 -2.6 MJ/kg CO 2 ) and 50% higher cyclic capacity than 30 wt% MEA.…”
Section: Introductionmentioning
confidence: 99%